MELEK AL-QUR’AN; BERCERMINKAN KARAKTER NABI IBRAHIM AS - Surasman, Otong (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2016)
At the beginning of 2016, it is expected that Indonesian Muslims are literate Quran in the broadest sense. Up to now as informed in various media, the majority of Indonesian Muslims are Quran illiterate. To be Quran literate, they have two duties, being able to read the Quran well and properly, and comprehending its contents. Firstly, to read Quran well and properly in short time, use the BBM (Easy Read Well) As Surasmaniyyyah Method, with a limit of twenty meetings capable of delivering smooth reading of the Quran and understanding the principles of tajweed/procedure for reading Quran. Further, understand well the character of Prophet Ibrahim immortalized in the Quran.